Who are poor and do they remain poor? - Geoffrey M. Ducanes; Edita Abella Tan (University of the Philippines, School of Economics (UPSE), 2014)
This paper examines the link between poverty and income, on the one hand, and human capital and location, on the other. In the process, the paper proposes a shift in the household indicator of human capital from the usual education of the household head to the education of the most educated member. The paper finds poverty to be most severe and persistent for households with low human capital, and that the effect of human capital varies substantially across locations. Additionally, the paper finds that low human capital households tend to underinvest in the human capital of school-age members, thus likely perpetuating poverty.
Keywords: I32; J24; I21; R11; 330; human capital; poverty; chronic poverty; regional development; enrolment rates